(untitled) (Ilm fan taraqqiyotida raqamli iqtisodiyot va zamonaviy ta’limning o’rni hamda rivojlanish omillari, 2025)
The development of the socio-economic spheres of our republic, further improvement of the quality of personnel training in the system of higher and secondary specialized, higher education; increasing students’ inquisitiveness, creativity, thinking abilities, and speech culture in vocational training based on modern achievements of science, technology, and technology; purposeful and effective use of information and communication technologies in mastering the secrets of professions; formation of students’ skills for independent work is one of the most pressing problems of today.